Physiological Linkage of Dyadic Gaming Experience. (February 2014) - Järvelä, Simo; Kivikangas, J. Matias; Kätsyri, Jari; Ravaja, Niklas
Dyadic gaming experience was studied in a psychophysiological experiment where conflict structure and the presence of an artificial intelligence (AI) agent in a turn-based game were varied in four different conditions. Electrocardiographic and electrodermal activity signals of 41 same-gender dyads were recorded to study joint changes in their physiological signals. A strong physiological linkage was found within dyads in all conditions, but the linkage scores did not differentiate between conflict modes. The only significant difference in linkage between conditions was an increase when the AI agents were not present. In addition, linkage was associated with different self-report scales assessing social presence. These results suggest that social presence and physiological linkage within dyads are higher when dyads can focus on each others' actions without distractions.